Dynamics of Hepatitis B Virus Pregenomic RNA in Chronic Hepatitis B Patients With Antiviral Therapy Over 9 Years - Pan, Jiali; Tian, Yu; Xu, Jinghang; Luo, Hao; Tan, Ning; Han, Yifan; Kang, Qian; Chen, Hongyu; Yang, Yuqing; Xu, Xiaoyuan (Frontiers in Medicine, 2022)
Serum hepatitis B virus pregenomic RNA (HBV pgRNA) is a potential biomarker that is correlated with covalently closed circular DNA. The long-term dynamics of HBV pgRNA in patients with chronic hepatitis B need to be explored. One hundred naïve nucleos(t)ide analog-treated patients with chronic hepatitis B were enrolled to analyze the dynamics of HBV pgRNA over 9 years. The positive rates of HBV pgRNAs declined gradually and showed biphasic kinetics. Serum HBV pgRNA levels in patients treated with entecavir became negative later than those treated with adefovir or lamivudine. Patients who remain positive for HBV pgRNA after 9 years of treatment may have higher viral transcription efficiencies. The reverse transcription efficiency of hepatitis B e-antigen (HBeAg)-positive patients was higher than that of HBeAg-negative patients at baseline and showed no difference after 24-week nucleos(t)ide analog treatment. The trajectory of serum HBV pgRNA-negative transformation differs in patients with different characteristics. Long-term dynamic monitoring of serum HBV pgRNA levels has significance in hepatitis B treatment.